Rapid formation of 2-lithio-1-(triphenylmethyl)imidazole and substitution reactions in flow - Wang,S; Panayides,J-L; Riley,D; Tighe,CJ; Hellgardt,K; Hii,KKM; Miller,PW (Reaction Chemistry and Engineering, 2021)
The functionalisation of imidazoles is a necessary step in the formation of many active pharmaceutical intermediates. Herein, we report a flow chemistry approach for the rapid and efficient formation of 2-lithio-1-(triphenylmethyl)imidazole at ambient temperature and its reaction with a range of electrophiles, achieving modest to high yields (40–94%) in short reaction times (<1 min). The method is amenable to the scale-up of this highly reactive lithio-imidazole intermediate.